From COVID-19 to COVID-666: Quasi-religious mentality and ideologies in Nigerian coronavirus pandemic discourse. (1st September 2021) - Chimuanya, Lily; Igwebuike, Ebuka Elias
In response to the global outbreak of the COVID-19 pandemic, different religious-immune conspiracy theories emerged to explain the increasing scary situation in Nigeria. Emerging multifarious narratives of the contagion, which are embedded in peculiar Nigerian socio-religiosity and religious economy, reconstructed the discourses into two complexities: corona disease is an invention of the devil and other dark evil forces, and corona disease is a sign of the end of times. The obvious fabrications escalated uncertainties surrounding the pandemic as well as generated anxiety and fears among potential believers who sermonize spiritual vigilance for the 'final battle and journey'. Drawing insights from critical discourse analysis, moral panic and frame theory, this study explores discursive means through which the pandemic is represented and reconstructed as long-awaited 'doomsday' warning in Nigerian online communities. Findings reveal instances of varying descriptive names, lexical derivations and discursive frames that reflect counter belief and quasi-religious ideologies. The study argues that complex religious doctrines rooted in antichrist or mark of the beast view, socio-religious ideologies of dominionism and overcommernism, cultural and personal linguistic processes have all contributed in shaping and institutionalizing the viral 'apocalyptic' world-view of the outbreak.